PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MAKANAN DAN MINUMAN : THE INFLUENCE OF CORPORATE GOVERNANCE AND LEVERAGE ON ACCOUNTING CONSERVATISM IN FOOD AND BEVERAGE COMPANIES - Saraswati, Atikah; Prajanto, Agung (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study examines the impact of corporate governance mechanisms and leverage on accounting conservatism in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019-2023. Employing a quantitative approach with a sample of 113 companies, data was collected from financial reports and analyzed using multiple linear regression. The results indicate that corporate governance mechanisms and leverage significantly influence accounting conservatism. Specifically, institutional ownership, audit committees, and leverage have significant positive effects. Conversely, independent commissioners, managerial ownership, and board size have insignificant impacts. These findings underscore the importance of effective corporate governance implementation to enhance financial report transparency and accountability.